Further Evidence for a Humoral Control of Factor VIII Plasma Levels - Landaburu, Ricardo H.; Castellanos, Delicia E. (Thrombosis and Haemostasis, 1973)
Factor VIII increase after stress or adrenergic stimulation appears to be justified by ACTH release, which in turn liberates a principle other than steroids, from the adrenal cortex. A substance isolated from adrenal cortex and denominated S3 increase, when injected, the level of plasma factor VIII. The rise in factor VIII after S3 also occurs in adrenalectomized animals where ACTH or catecholamines administration gives negative results.